Sistemas de cultivo para a cultura de melancia - Rocha, Marta Rodrigues da (2010)
Aiming to evaluate the watermelon crop (Citrullus lanatus L.) in different management systems, on an Ultisol in the Central Depression of RS, Brazil, an experiment was carried out during the agricultural year 2008/2009 with the Crimson Sweet cv. The climate of the area is subtropical humid "Cfa" without drought (Köeppen), with annual rainfall of 1382 mm. With experimental units of 48 m² and random blocks design with 4 repetitions, the following management systems were tested: conventional tillage (CT), no-tillage (NT), NT chiseled with one chisel shank (NT1S), NT chiseled with two chisel shanks side by side (NT2S), NT chiseled with three chisel shanks side by side (NT3S), NT chiseled with four chisel shanks side by side (NT4S), NT chiseled with five chisel shanks side by side (NT5S); the chisel shanks were 0,35 m. The data were a nalysed by the Duncan test (P <5%). The watermelon was sowed in November 2008, with spacing of 2,20 x 0,75 m, on black oat straw (Avena strigosa). Besides the watermelon productivity, considering the marketable fruits (> 6 kg), were determined fruits quality parameters (total soluble solids, pH and titratable acidity), root superficial area and root system distribution in soil profile, perpendicular of the sowing line (30 and 60 days after sowing), using the program SIARCS® of EMBRAPA. Besides, were determined some soil physical properties after watermelon cycle (soil density, porosity, aggregation, resistance to penetration and instantaneous water infiltration rate). CT obtained the larger productivity (126 Mg ha-1), differing statisticaly of the other treatments. The medium weight and the fruits quality parameters were not affected by the soil management systems. The roots total area was increased with mobilization intensity and soil mobilized area, except for the treatment NT4S. In the treatment CT, the soil density didn't show difference in depth, but in the other treatments there was difference among the layer 0 0,05 m and the deepest layers. The largest macroporosity was found in the layer 0 0,10 m, while the resistance to the penetration in this same layer was smaller, what might have favored the roots largest concentration found in that layer. For the instantaneous water infiltration rate, measured in the sowing line, the largest values were found in the treatments NT3S and NT5S, differing of NT.